Prevalence of deleter habits and malocclusions in mixed dentition in children of the city of Quito, Ecuador - Lopez Gallegos, E (2018)
Objective: To determinate, the prevalence of malocclusions in mixed dentition of children from 6 to 12 years of age, from two schools in the city of Quito- Ecuador. Materials and methods: through visual observation, 143 children were examined with respect to the type of occlusion. The identification data of the participants about specific questions about the most frequent habits were collected in previously prepared files, the data were subjected to descriptive and statistics test. Results: the descriptive analysis showed that only 17% of the children had the characteristics of a normal occlusion, the remaining 83% had some type of malocclusion. Within the malocclusion, labial suction was the most prevalent with 16,1% of the entire sample. Class I molar and canine was the most frequent. Class molar I and canine was the most frequent. Chi square analysis determined that there is no dependency relationship between the type of habit and the prevalence of anterior open bite (p=0,69), whit a slightly higher proportion when considering labial suction. Conclusion: The prevalence of malocclusions in the studied population was high, being the habit of lip suction the most prevalent.